A career in statistics : beyond the numbers - Hahn, Gerald J.; Doganaksoy, Necip, 1960- (Hoboken, N.J. : John Wiley & Sons, 2011)
'This book serves as an excellent companion to its predecessor, The Role of Statistics in Business and Industry. In this volume, the authors help readers decide whether a career in statistics is appropriate for them and what to expect once in it. They provide insights into the work environment and how students and entry-level statisticians can best prepare themselves to succeed, offering hints for success in training, career paths, and lifelong learning. This book is a must-have for anyone considering a career in statistics, as well as for faculty who prepare students for such a career'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Mathematical statistics; Commercial statistics; Statistics -- Vocational guidance; Statisticians -- Vocational guidance